THE EFFECT OF COMPANY SIZE AND BUSINESS RISK ON CAPITAL STRUCTURE IN AUTOMOTIVE INDUSTRY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Wairooy, Mohamad Ali (Jurnal Ekonomi Balance, 2019)
This study aims to examine and analyze the effect of partially or simultaneously the size of the company and business risk on the capital structure of the Automotive Industry Company Registered on the Indonesia Stock Exchange. Data collection uses secondary data using purposive sampling technique. The population in this study were all automotive industry companies as many as 17 companies listed on the Indonesia stock exchange for the period 2014-2016, while the samples taken were the number of observations for 3 years (2014-2016). The data obtained were analyzed using multiple linear regression analysis. The results showed that all hypotheses had a positive and significant effect based on t test and F test. This means that both partially and simultaneously the size of the company and business risk had a positive and significant effect on the capital structure of the Automotive Industry Company Listed on the Indonesia Stock Exchange.